Employee Commitment and Organizational Policies at PT PLN (Persero) UP3 Surakarta - Anton Agus Setyawan; Dea Pradita Kumalasari (Proceedings International Conference on Sustainable Innovation (ICoSI), 2023)
PT. PLN represents one of BUMN's moving in the field of ready electric power which it's existence is very required by society. Thereby PT. PLN claimed to provide electric power which with quality is good the than facet sum up and also the quality. Others PT. PLN is also claimed to give professional service to customers or society. Along with that's writer has an eye to perform research with the title "Employee Commitment and Organizational Policies PT PLN (Persero) UP3 Surakarta”. State-owned enterprises need to be more community-friendly as a form of public organization. The orientation of state-owned enterprises so far has tended to be towards national interests (bureaucracy), which has led to an unhealthy condition of state-owned enterprises in Indonesia, giving rise to widespread social debate. Purpose and objectives to analyze employee attitudes, roles, and commitment to the work team. This type of research uses quantitative methods. The population in this study were employees of PT PLN (Persero) UP3 Surakarta. There are three variables in this study, namely the dependent, independent, and mediating variables. The results of this study, the commitment variable has a significant effect on organizational behavior.